Relationship between Accuracy, Speed, and Consistency in a Modern Pentathlon Shooting Event - Jongchul Park; Seunghun Lee; Sabin Chun (Applied Sciences, 2022)
In the modern pentathlon, the laser run is the highest influence on the results, and fast and accurate shooting is essential. This study evaluates the relationship between shooting characteristics (shot speed, consistency, accuracy) according to sex, competition type, and round number during laser run competitions among 19,648 modern shooting round cases from 2015 to 2019. As a result, men showed faster shot speed than women (p < 0.05, d = 0.493), and final rounds were significantly better than qualifier round in shot speed (p < 0.05, d = 0.176), consistency (p < 0.05, d = 0.138), and accuracy (p < 0.05, d = 0.151). Series-1 had the highest consistency (p < 0.05, <semantics><msubsup>ηp2</msubsup></semantics> = 0.01) and accuracy (p < 0.05, <semantics><msubsup>ηp2</msubsup></semantics> = 0.07) compared to other series. Series-4 had the lowest shooting speed (p < 0.05, <semantics><msubsup>ηp2</msubsup></semantics> = 0.01) compared to other series. Consistency and speed showed moderate positive correlation (r = 0.362, p < 0.05). These results show differences in shot characteristics according to sex, competition type, and round number, and explain the relationship between shot speed and consistency. We believe these results will help relevant coaches and players aiming to improve performance understand shot characteristics and reduce shot time.